2014
DOI: 10.1007/s10840-014-9889-8
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and ablating stable sources for atrial fibrillation: summary of the literature on Focal Impulse and Rotor Modulation (FIRM)

Abstract: Atrial fibrillation (AF) is the most common sustained arrhythmia and the most common indication for catheter ablation. However, despite substantial technical advances in mapping and energy delivery, ablation outcomes remain suboptimal. A major limitation to AF ablation is that the areas targeted for ablation are rarely of proven mechanistic importance, in sharp contrast to other arrhythmias in which ablation targets demonstrated mechanisms in each patient. Focal impulse and rotor modulation (FIRM) is a new app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
1
19
2
Order By: Relevance
“…More recently, some specific strategies of substrate ablation have proved to be interesting, including ganglionic plexus 21,22 and rotor ablation procedures. 23,24 While we await more trial data, it is interesting that this second-generation cryoballoon creates lesions that are near the ganglionic plexi on the LA posterior wall. 21 Additionally many stable rotors have been found near the "PV ostia-to-LA antrium" border which is contiguous with the area of cryoballoon ablation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, some specific strategies of substrate ablation have proved to be interesting, including ganglionic plexus 21,22 and rotor ablation procedures. 23,24 While we await more trial data, it is interesting that this second-generation cryoballoon creates lesions that are near the ganglionic plexi on the LA posterior wall. 21 Additionally many stable rotors have been found near the "PV ostia-to-LA antrium" border which is contiguous with the area of cryoballoon ablation.…”
Section: Discussionmentioning
confidence: 99%
“…The algorithm/ablation procedure used by Narayan et al was called focal impulse and rotor modulation (FIRM). Based on the outcome of the clinical studies on FIRM-guided ablation and several other follow-up studies, the FIRM algorithm was found to be effective, especially when combined with PVI [53]. The FIRM technology was later commercialized as a clinical diagnosis system for AF, now owned by Abbott Electrophysiology.…”
Section: Computer-aided Technologies For Atrial Fibrillationmentioning
confidence: 99%
“…This widely circumferential extension of the cooling area may provide collateral benefit by ablating local contributors in AF triggering and maintenance such as ganglionic plexi and rotors, which may have therapeutic implications among patients with persistent AF [17, 44, 45]. …”
Section: Strengths and Limitations Of The Cryoballoon In Persistent Amentioning
confidence: 99%